Novinari i novinarstvo / Journalists and Journalis: Percepcija studenata, novinara i javnosti / Student: Journalist and the Public Perception - Silajdžić, Lamija (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
Given the fact that the journalism as a profession is constantly publicly observed and that it affects all parts of society, it is necessary to question how it is perceived in society. Although the circumstances of the journalistic profession are changing, it still exists as a socially necessary profession that is important to all citizens, because it finds processes and communicates information relevant to the life of every individual in society. This paper examines the attitudes of students of journalism, journalists and the public about journalism and the role of journalists in society. This approach was chosen in order to get a more complete insight of the position of journalists in the Bosnian and Herzegovinian society and what is the perception of different subjects about the journalistic profession. Given the fact that journalism has a very important role in society as a gate-keeper or fourth pillar of government, it is necessary to maintain its credibility and to make the public aware of the importance of the professional work of journalists for society. The results of this research have shown that both students (future journalists), professional journalists, as well as the public, think that the situation in Bosnian and Herzegovinian journalism is bad or average, and that this is influenced by both external and internal factors.